1988
DOI: 10.1002/ana.410230734
|View full text |Cite
|
Sign up to set email alerts
|

Spastic paraparesis and HTLV-I infection in peru

Abstract: Three of 6 patients with spastic paraparesis in Lima, Peru, were found to have antibodies to human T-lymphotropic virus type I (HTLV-I). Blood and cerebrospinal fluid antibodies were confirmed by Western blot analysis. Multilobulated lymphocytes in blood and cerebrospinal fluid of the index case stained with monoclonal antibodies for T-helper cells and for T10, an activation marker. Blood mononuclear cells from patients with HTLV-I-associated myelopathy showed spontaneous proliferation in culture, evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1989
1989
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…In view of a strong association of positive serology for syphilis and the inflammatory changes in the CNS, it was originally thought that the most likely cause of TSP was a Treponemu pulidum infection. However, recent studies have demonstrated the presence of antibodies to HTLV-I in blood and CSF [6] and oligoclonal I& to HTLV-I in CSF { S , 81. The virus has now been isolated from TSP material and has been demonstrated immunocytochemically and ultrastructurally in T-cell lines derived from the peripheral blood and CSF of several patients E91.…”
Section: Discussionmentioning
confidence: 99%
“…In view of a strong association of positive serology for syphilis and the inflammatory changes in the CNS, it was originally thought that the most likely cause of TSP was a Treponemu pulidum infection. However, recent studies have demonstrated the presence of antibodies to HTLV-I in blood and CSF [6] and oligoclonal I& to HTLV-I in CSF { S , 81. The virus has now been isolated from TSP material and has been demonstrated immunocytochemically and ultrastructurally in T-cell lines derived from the peripheral blood and CSF of several patients E91.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 mainly infects inhabitants of southern Japan 16,41 , equatorial Africa 8 , Malasia 50 , the Caribbean 6 , South America (Brazil 34 , Colombia 51 , Peru 19 , Chile 44 , Argentina 14 , and Uruguay 28 ), and the southern United States 5,46 . In Brazil, since the introduction of HTLV-1 screening tests in blood centers, the virus has been found among blood donors with a prevalence varying from state to state.…”
Section: Introductionmentioning
confidence: 99%
“…In 1988, Johnson and col. reported cases of TSP in Peru affecting residents living in a region not known to be endemic and in Caucasians who had no previous history suggestive of contamination by the HTLV-I virus 9 .…”
Section: Commentsmentioning
confidence: 99%